Effective Language Learning - Nazarova Navbahor Ahrorovna; Akhmedova Marjona (Genius Journals, 2022)
This article is dedicated to get acquainted with the term “effective language learning”, learners’ styles and features as well . Additionally , the article concentrates on scientific books, researches and its results which provide learners with opportunities to gain more understanding
Keywords: effective language learning; acquiring skills; approaches of learning; awareness of languages